Upaya Meningkatkan Keterampilan Berpidato dengan Metode Modeling The Way Secara Online di Kelas VI SDN Rembang 1 Kota Blitar - Nurkamsiyah (Civiliza Publishing, 2021)
Abstract. Learning Indonesian is a learning that has 4 aspects that must be achieved by students, namely aspects of writing, reading, listening, and speaking. In teaching speech in class VI, students must learn in compiling speech texts and in delivering the speech in public. Speech learning activities in Class VI SDN Rembang 1, Sanawetan District, Blitar City in semester 2 of the 2020/2021 Academic Year still show the lack of success of teachers in teaching to students, especially in online learning so there needs to be an appropriate learning method. This requires teachers to conduct research, while the research is used qualitatively on students in learning Indonesian. The type of research used is Classroom Action Research (CAR). Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The learning facilities used are learning using the Modeling The Way method, which is a teaching method carried out by the teacher providing a scenario for a sub-discussion to be demonstrated by students in front of the class.